Combinatory potential of contrastive discourse markers in English and Lithuanian: a semantic functional analysis - Maslauskienė, Greta (Lietuvių kalba, 2020)
Although numerous studies have concentrated on individual discourse markers (henceforth, DMs) or their classes, little attention has been paid to their combinations, especially from a cross-linguistic perspective. Most of the studies are based on the English language data, whereas the combinatory potential of DMs in other languages remains largely unexplored. The present corpus-based study focuses on combinations of contrastive discourse markers (henceforth, CDMs) in English and Lithuanian by adopting Fraser’s (2013) approach to DMs. The aim of the study is to investigate the combinatory potential of CDMs in English and Lithuanian academic discourse, spoken discourse and fiction. The study presents a list of CDM combinations used in English and Lithuanian and investigates their semantic-pragmatic profile.